Heidegger om Nietzsche – stilen som overset perspektiv - Pedersen, Fie Juul (Tidsskrift for Medier, Erkendelse og Formidling, 2018)
Denne artikel fokuserer på Nietzsches stil som et overset aspekt i Heideggers Nietzsche-læsning. Heidegger fremhæver begreberne Andenken (erindring), Verwindung (forvinding) og Ereignis (begivenhed) i sin egen tænkning og understreger, at disse er nødvendige for en tænkning, der ikke er metafysisk. Han finder ikke disse elementer i Nietzsches tænkning, men jeg vil argumentere for, at de findes hos Nietzsche, men at Heidegger ikke har blik for dem, fordi de skal lokaliseres i stilen. Heidegger har ikke blik for Nietzsches filosofiske stil, hvilket resulterer i, at han fejlagtigt kategoriserer Nietzsche som rendyrket metafysiker. ABSTRACT This article focuses on Nietzsche’s style as an overlooked aspect in Heidegger’s reading of Nietzsche. Heidegger emphasises the concepts of Andenken (memory), Verwindung (incorporation) and Ereignis (event) in his own thinking and he underlines the importance of these in a non-metaphysical way of thinking. He does not find these elements in Nietzsche’s work, but I will argue that Nietzsche deals with these too. Heidegger does not notice this since they are found in Nietzsche’s style. Heidegger has no regard for the philosophy in Nietzsche’s style and this causes him to wrongly characterize Nietzsche as simply a metaphysician.